Az eurorégiók szerepe a határok lebomlásában - Székely, Andrea (Közép-Európai Közlemények, 2010)
The Vah-Danube-Ipel Euroregion (founded in 1999) has an area of 24 thousands of km2, so it is among the largest euroregions around Hungary. Its area is larger than regions in Slovakia and Hungary; and two smaller euroregions has been founded within its boundaries. Now, we investigate by official and scientific definitions whether the Vah-Danube-Ipel Euroregion can fulfil its function at regional level. The aim of the research is to explain the role of the city Székesfehérvár in the Vah-Danube-Ipel Euroregion. The city of Székesfehérvár is the capital of Fejér county, and at the same time, is the center of the Middle-Trans-Danubian region accommodating three counties: Fejér, Veszprém, and Komárom-Esztergom. Neither Székesfehérvár, nor Fejér county are not directly located on the border. Consequently their role in the cross-border cooperation can be realised only through regional level organisations.